The Relationship between Foreign Direct Investment, Exchange Rate, and Broad Money Growth: The case of Nigeria - Aliyu, Habib Isa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The thesis investigates the long-run equilibrium relationship between foreign direct investment, exchange rate, and broad money growth in the case of Nigeria with the use of data sourced from the World Bank Development Indicators from 1970 to 2016. The thesis applies the two unit root tests namely Augmented Dickey-Fuller and Phillips–Perron in order to test the stationarity of the variables with Kwiatkowski– Phillips–Schmidt–Shin stationarity test as a confirmatory test. Vector autoregressive model (VAR) is applied along with Johansen cointegration test and vector error correction model (VECM) with the aim of estimating the long-run coefficients and determining the existence of a long-run association between the variables. Granger causality test is further applied to determine the directions of the variables and lastly, Impulse Response Function and Variance Decomposition are applied to see the variables’ response to an exogenous shock. The results indicate a positive long-run relationship between FDI and broad money growth as well as a negative long-run relationship between exchange rate and broad money growth in Nigeria. The thesis recommends policymakers to adopt a suitable exchange rate regime other than the floating or flexible regime, target inflation with monetary policy and narrow down the gap that exists between inter-bank and parallel market foreign exchange rate. Furthermore, local production, as well as exports, need to be boosted and imports should be reduced by levying more tax on luxury imports. There should also be a provision of foreign exchange futures for investors in order to stimulate foreign investment.

ÖZ: Bu tez, Dünya Kalkınma Bankasından 1970 ve 2016 yılları arasında elde edilen veriler kullanılarak, Nijerya’da doğrudan yabancı yatırım, döviz kurları ve geniş para büyümesi arandaki uzun vadeli dengeilişkisini incelemektedir. Bu tezde değişkenlerin durağanlığını test edebilmek için Augmented Dickey-Fuller, Phillips-Perron ve Kwiatkowski-Phillips-Schmidt – Shin durağanlık testi olmak üzere üç birim kök testi uygulanmıştır. Ayrıca değişkenlerin uzun vadeli katsayılarını tahmin etmek için Vektör hata düzeltme modeli (VECM) kullanılmıştır. Granger nedensellik testi ise değişkenler arasındaki ilişkilerin yönünü belirlemek için kullanılmıştır. Son olarak, dürtü yanıt fonksiyonu ve değişken ayrıştırma yöntemleri, değişkenin dış şoklara vereceği tepkileri inceleyebilmek için kullanılmıştır. Sonuçlar, Nijerya’da doğrudan yabancı yatırım ve geniş para büyümesi ile uzun vadede olumlu; fakat döviz kurları ve geniş para büyümesi ile uzun vadede negatif bir ilişki olduğunu göstermiştir. Bu tez, politikacıların dalgalı ve esnek bir rejimden çok uygun bir döviz kuru rejimi benimsemesini, para politikasıyla enflasyonun kontrol altına alınıp bankalar arası ve paralel piyasa döviz kuru arasındaki boşluğun daraltılmasını, ithalatın önemli ölçüde azaltılarak yerel üretimin desteklenmesini ve ihracata hız verilmesini önermektedir.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2018. Co-Supervisor: Assoc. Prof. Dr. Korhan Gökmenoğlu, Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Foreign Direct Investments--Nigeria; Broad money growth; Foreign Direct Investment; Exchange rate; Thesis Tez; Banking and Finance Department